Regional geographic variations in kidney cancer incidence rates in European countries - Li, Peng; Znaor, Ariana; Holcatova, Ivana; Fabianova, Eleonora; Mates, Dana; Wozniak, Magdalena B; Ferlay, Jacques; Scelo, Ghislaine (European urology, 2015)
CONTEXT: Marked unexplained national variations in incidence rates of kidney cancer have been observed for decades in Europe. OBJECTIVE: To investigate geographic variations at the regional level and identify European regions with high incidence rates of kidney cancer. EVIDENCE ACQUISITION: Regional- and national-level incidence data were extracted from the Cancer Incidence in Five Continents databases, local cancer registry databases, and local published reports. World population age-standardised rates (ASRs) were calculated for the periods 2003-2007 and 1988-1992. Rates by period and sex were compared using map visualisation. EVIDENCE SYNTHESIS: During 2003-2007, the highest ASR was found in the Plzen region, Czech Republic (31.4/100,000 person-years in men). Other regions of the Czech Republic had ASRs of 18.6-27.5/100,000 in men, with a tendency for higher rates in regions south of Prague. Surrounding regions, including eastern Germany and regions of Slovakia and Austria, had medium-to-high incidence rates (13.0-16.8/100,000 in men). Three other areas in Europe showed higher incidence rates in men compared with the rest of the continent: Lithuania, Estonia, Latvia, and Belarus (15.0-17.6/100,000); Iceland (13.5/100,000), and northern Italy (up to 16.0/100,000). Similar regional differences were observed among women, with rates approximately half of those observed in men in the same region. In general, these regional geographic variations remained stable over the periods 1988-1992 and 2003-2007, although higher incidence rates were detected in the Baltic countries in 2003-2007. CONCLUSIONS: Several European regions show particularly high rates of kidney cancer incidence. Large variations were observed within countries covered by national health-care systems, implying that overdetection is not the major factor. PATIENT SUMMARY: We present regional geographic variations in kidney cancer incidence rates in Europe. We highlight several regions with high incidence rates where further studies should be conducted for cancer control and prevention.
Keywords: programy národního zdraví; Male; National Health Programs; Evropa; Time Factors; Europe; Sex Factors; časové faktory; Humans; rizikové faktory; Kidney Neoplasms; mužské pohlaví; Female; ženské pohlaví; incidence; Incidence; sexuální faktory; nádory ledvin; lidé; Risk Factors